Tracking adult stem cells - Snippert, Hugo J (Nature Publishing Group, 2011)
The maintenance of stem-cell-driven tissue homeostasis requires a balance between the generation and loss of cell mass. Adult stem cells have a close relationship with the surrounding tissue—known as their niche—and thus, stem-cell studies should preferably be performed in a physiological context, rather than outside their natural environment. The mouse is an attractive model in which to study adult mammalian stem cells, as numerous experimental systems and genetic tools are available. In this review, we describe strategies commonly used to identify and functionally characterize adult stem cells in mice and discuss their potential, limitations and interpretations, as well as how they have informed our understanding of adult stem-cell biology. An accurate interpretation of physiologically relevant stem-cell assays is crucial to identify adult stem cells and elucidate how they self-renew and give rise to differentiated progeny.